PERHITUNGAN STRUKTUR BETON BERTULANG GEDUNG PERKULIAHAN 7 LANTAI UNIVERSITAS TANJUNGPURA PONTIANAK - Hendra Ardi Lesmana; M. Yusuf; Gatot Setya Budi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Structural design is the primary aspect of civil engineering. The very basic of construction of any building, residential house, dams, bridges, culverts, canals etc. is designing. The foremost basic in structural engineering is the design of simple basic compinents and members of a building viz, Slabs, Beam, Coloumns and Footing. For their design, an architectural design is prepared using the Auto CAD. In order to design them, it is important to first obtain the plan of the particular building that is, positioning of the particular rooms such that they serve their respective purpose and also suiting to the requirement and comfort of the inhabitants. Thereby depending on the suitability, plan layout of beams and the position of columns are fixed. Thereafter, the vertical loads are calculated namely the dead load and live from SNI 1726:2012. In this project, the design of 7 floors classroom building is done according to the Indonesian National Standart. SNI 2847:2013 has been used for the reinforment design, SNI 03-1727-1989  has been used for the estimation of all the load on structure viz, Dead Load, and Live Load and SNI 1726:2012 has been used for the estimation of earthquake load. Once the loads are obtained, the slabs are designed. Designing of slabs depends upon whether it is one-way or two-way slab, the end conditions and the loading. The alanlysis and designing of beams and colums are done by the “ETABS” software tool. The footings are designed manually, after completion of designing the detailed estimation has to be carried out.   Keyword: SNI 2847:2013, Reinforced Concrete Structure, 7 Floors Classroom Building